Shrinkage of self-compacting concrete. A comparative analysis - Oliveira, Miguel José (2019)
Self-compacting concrete (SCC) is a concrete type that does not require vibration for placing and compacting. SCC possesses special technical features and properties that recommend its application in many jobs. Nevertheless, in some situations, it has been observed an inadequate behaviour of the material at early ages due to shrinkage. The existing shrinkage prediction models were developed for standard concrete. In this paper three SCC mixtures, with different compressive strength, are studied in terms of autogenous and total shrinkage. The results are compared with the Eurocode 2 model. For the studied mixtures it was found that this model underestimates the autogenous shrinkage, while the total shrinkage is generally overestimated.